Young Tend to Commit Suicide, Die of Road Traffic Accidents or being Killed by Someone: an Analysis of Medico-Legal Deaths - Vidanapathirana, M (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Background: Young people tend to get aggressive or depressed and may risk their lives. This research was done to describe the associations of demographic findings with causes and postmortem findings of medico-legal deaths. Methods: Descriptive cross-sectional study of all deaths reported to a selected tertiary care hospital in Colombo Sri Lanka from 1st of Janauary-2011 to 31st of December-2012 was conducted. Results: Out of 1502 postmortems 67.3% were natural deaths, 16.8% accidents, 6.1% suicides and 3.5% homicides. Majority (54.5%) were ‘pre-mature’ deaths (<60 years) with mean age of 54.4 (+/-19.1). Majority (71.4%) were males. Majority (47.7%) were non-communicable diseases and were 16.6% and 52% in =<30 and >30 years of age respectively (P<0.01). Cardio vascular system accounted for 40.7% deaths and was associated with both age and sex (P<0.01). The most common course of death was ischemic heart disease (22.9%) and was also associated with age (P<0.01). Out of 887 natural deaths only 170 were infectious communicable diseases, out of which 89 were respiratory causes. Road traffic accidents accounted for 171 deaths and were 17.1% and 10.6% respectively among =<30 and >30 years (P<0.01). There were 34 train injury deaths and were 4.1% and 0.9% respectively among 5 police stations along the coastal railway line and other 10 police stations (P<0.01). There were 50 suicides by hanging and were associated with age (P<0.01) but not with gender or ethnicity (P>0.05). There were 46 homicides and were 7.8% and 2.4% among =<30 and >30 years respectively (P<0.01) but were not associated with gender and ethnicity (P>0.05). Conclusion: Non-communicable disease was the leading cause of mortality. Majority were ‘premature deaths’. Communicable diseases were dominant only in respiratory deaths. Adults more than 30 years old tend to die of non-communicable diseases especially by cardio vascular system causes such as ischemic heart disease. Young people less than 30 years old tend to die of road traffic accidents, commit suicide by hanging or being killed by someone. Limitation of access to railway lines in order to reduce the railway deaths is recommended. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE TA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->